2021
DOI: 10.3390/ijerph18179276
|View full text |Cite
|
Sign up to set email alerts
|

Will Anti-Epidemic Campus Signals Affect College Students’ Preparedness in the Post-COVID-19 Era?

Abstract: The COVID-19 pandemic has been a tremendous global threat and challenge for human beings, and individuals need to be prepared for the next wave of the outbreak, especially in the educational setting. Limited research has focused on individual knowledge, awareness, and preparedness of COVID-19 in postsecondary institutions in the post-COVID-19 era so far. This study aimed to explore whether students’ perceived anti-epidemic campus signals had effects on their awareness of and preparedness for COVID-19. Leveragi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 36 publications
2
9
0
Order By: Relevance
“…Male students were more knowledgeable about COVID-19 than their female peers. This finding was consistent with that of a previous study conducted in China with a larger undergraduate student sample including 13 universities and colleges [ 14 ]. In Bangladesh, Hossain et al [ 24 ] found that men aged from 13 to 88 scored higher on knowledge of COVID-19 than women.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Male students were more knowledgeable about COVID-19 than their female peers. This finding was consistent with that of a previous study conducted in China with a larger undergraduate student sample including 13 universities and colleges [ 14 ]. In Bangladesh, Hossain et al [ 24 ] found that men aged from 13 to 88 scored higher on knowledge of COVID-19 than women.…”
Section: Discussionsupporting
confidence: 93%
“…These three protective measures, in addition to getting vaccinated against SARS-CoV-2, represent the four protective behaviors that were examined in the model. Additionally, past literature has documented that there were differences in COVID-19 awareness, knowledge, and protective behaviors between the sexes [ 12 , 14 , 15 , 16 ]. Thus, this study also examined the sex differences in the intended variables as well as the relationships/paths in the tested model.…”
Section: The Present Study and Rationalementioning
confidence: 99%
“…This is perhaps because COVID-19 prevention supplies and materials such as masks and hand sanitizer are not expensive; the COVID-19 tests and vaccines, which are covered by government finances, are free; and, even if individuals have COVID-19, the government will pay for all the treatments. Additionally, an individual's sex seems to be a good predictor in predicting awareness, preparedness, and responses to campus anti-epidemic climate change, which is partially consistent with Zhao et al, observing that girls had higher awareness and better preparedness than boys ( 37 ). Perhaps this may be because women are aware that they are in nature physically weaker than men and thus have higher intentions to avoid high risks ( 38 ), leading them to be more sensitive to campus anti-epidemic climate change, and avoid campus activities that may have large public gatherings.…”
Section: Discussionsupporting
confidence: 80%
“…In the lens of gender, Pinchoff et al also found that COVID-19 had disproportionately impacted young girls and women in terms of knowledge and preventive behaviors [ 12 ]. Zhao et al highlighted the significant relationships between sex and students’ COVID-19 knowledge and preparedness [ 13 ]. All together, these studies indicated that it was important to understand among young adults how sex played roles in responding to the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…This might add a sex-related lens in adolescents and young adults to the existing literature as suggested by Gausman & Langer [ 3 ]. In addition, to our knowledge, insufficient empirical results have been found to inform postsecondary institution stakeholders whether young females are more prepared for and better respond to COVID-19, or their counterparts, despite a few [ 12 , 13 ], especially in the Chinese context. So far, an increasing number of scholars have examined how individuals psychically respond to COVID-19, such as awareness, knowledge, prevention behaviors, and preparedness, but limited research focuses on how they respond to institutional climate/policy changes.…”
Section: Introductionmentioning
confidence: 99%